Clinical features and oncologic outcomes of primary retroperitoneal ganglioneuroma: a retrospective cohort study of 51 patients from a high-volume sarcoma center - Li, Wenjie; Xiao, Mengmeng; Miao, Chengli; Zou, Boyuan; Liu, Shibo; Huang, Mei; Gao, Haicheng (Frontiers in Surgery, 2025)
BackgroundRetroperitoneal ganglioneuroma (RGN) is a rare, benign tumor derived from neural crest cells of the sympathetic nervous system. Due to its rarity and complex management, clinical understanding remains limited. This study aimed to analyze the clinical features and surgical outcomes of RGN.MethodsA retrospective analysis was performed utilizing the retroperitoneal tumor database of Peking University International Hospital. Patients who underwent surgical resection for pathologically confirmed primary RGN between January 2015 and August 2024 were included. Systematic postoperative follow-up was conducted to assess outcomes.ResultsFifty-one consecutive patients (18 males, 33 females; median age 28 years, range 12–73) with newly diagnosed RGN were enrolled. Clinical presentations were heterogeneous: 29 cases (56.9%) were incidental findings on physical examination, 16 (31.4%) reported abdominal discomfort, 3 (5.9%) had lumbago, and single cases presented with hematuria, chest tightness, or lower limb pain. R0/R1 resection was achieved in 45 patients (88.2%). Postoperative complications occurred in 11 patients (21.6%), including gastroparesis (n = 3), pancreatic fistula (n = 3), liver function impairment (n = 2), wound infection (n = 2), and one mortality due to intestinal ischemia and necrosis. Histopathology confirmed GN in all cases. At median follow-up of 62 months (90.2% follow-up rate), no recurrences, metastases, or disease-specific deaths occurred—including in R2 resection patients (n = 6).ConclusionsRetroperitoneal ganglioneuroma (RGN) is a rare benign tumor that frequently presents with nonspecific symptoms. While surgical resection remains the cornerstone of management, it is best undertaken at specialized, high-volume sarcoma centers to mitigate operative risks. When complete excision is precluded by critical vascular involvement, subtotal resection represents a judicious alternative. For selected patients with small, asymptomatic tumors—particularly those with elevated surgical risk—active surveillance is a reasonable option. Despite a generally favorable prognosis, long-term follow-up is recommended.